Indian and Universal Spirituality in the Thought of Shri Ramakrishna: Exploring Shri Ramakrishna's Spiritual Journey (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sri Ramakrishna Paramahamsa's spiritual adventure to Maha-samadhi remains a one of a kind involvement in the records of human accomplishment. Maybe couples in the cutting edge time have shown such God-inebriation and love for 'Mother' as a persevering enthusiasm in one lifetime. The way of God acknowledgment has been mind boggling, benevolent and requesting with the furthest points of human perseverance and torment, all of which the Ace continued with serenity. We are educated that the Ace was a manifestation of God Himself, and in this way lived in this world but then not of 'it'. However, every scene of his life was emblematic in that it remains a 'message' to humanity..Another translation may be that Ramakrishna concretised the Kabbalistic perspective, synchronizing what may be 'a definitive connection between the earthly domain of the universe and the earthbound domain of man. Living in the two universes, Sri Ramakrishna encountered the supernatural connections displayed by the real world religions, contending and building up past all sensible uncertainty that God is One.